Information Processes in Post-Revolution Armenia and Azerbaijan Propaganda - Nazaryan, Hayk (Bulletin of Yerevan University D: International Relations and Political Sciences, 2020)
The 2018 Armenian Revolution brought significant changes to the regional policy, allowing to newly evaluate regional political processes. Specifically, these transformations affected the ability of Armenia to set our own rules in Armenian-Azerbaijani information warfare. Armenian-Azerbaijani information warfare entered a new phase: new processes and issues of the Artsakh conflict brought up by Armenian side made Azerbaijan review their attitude toward the conflict: offensive strategy adopted by the new Armenian government shadowed the idea of swift victory served to Azerbaijani society for many years, new approaches of the Armenian side towards the information delivery reduced the efficiency of Azerbaijani propaganda, etc. At the same time, we are facing new challenges: Baku is taking serious steps towards creating a more comprehensive and diverse information policy. To meet these new challenges, and keep a high-resistant information environment, we need to create an information policy based on national interests and the national value system.